2007
DOI: 10.1111/j.1460-9592.2007.02381.x
|View full text |Cite
|
Sign up to set email alerts
|

Do not mask the mask: use it as a premedicant

Abstract: Playing with an anesthesia mask given during a preanesthesia visit relieved anxiety, improved mask acceptance quality and shortened the induction period. We believe that this type of premedication would be feasible in gaseous induction of anesthesia in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 24 publications
1
16
0
1
Order By: Relevance
“…However, children who were provided the intervention 1 week before surgery did not demonstrate significantly lower anxiety scores than children who did not receive the intervention (Walker et al, ). Conversely, in Aydin et al () study children in the intervention group who were given anesthesia mask to home for training before the day of surgery demonstrated a significantly lower level of anxiety at the time of anesthesia induction than children in the control group.…”
Section: Discussionmentioning
confidence: 90%
“…However, children who were provided the intervention 1 week before surgery did not demonstrate significantly lower anxiety scores than children who did not receive the intervention (Walker et al, ). Conversely, in Aydin et al () study children in the intervention group who were given anesthesia mask to home for training before the day of surgery demonstrated a significantly lower level of anxiety at the time of anesthesia induction than children in the control group.…”
Section: Discussionmentioning
confidence: 90%
“…By providing a shared focus for the child, parent and health professional, play can shift the attention away from the discomfort of medical treatment and create a potential for positive caregiver–child interaction [28]. In addition to being used by parents in our study, play has been found to motivate children to accept topical treatment [29] and inhalations [30]. …”
Section: Discussionmentioning
confidence: 99%
“…5,6 Presurgical anesthetic mask exposure is one non-pharmacological intervention that has demonstrated promising research support. [7][8][9][10][11][12] Nevertheless, most studies had methodological limitations (i.e., no comparison group or standardized measure of child anxiety). 7,8 An exception is a study by MacLaren and Kain, 12 who examined the efficacy of a brief, standardized, parent-directed anesthetic mask exposure and shaping protocol on the day of surgery against a control group who received standard care.…”
Section: Résumémentioning
confidence: 99%